School Readiness in Children Born <30 Weeks' Gestation at Risk for Developmental Coordination Disorder: A Prospective Cohort Study. Issue 5 (28th June 2022) - Spittle, Alicia J.; Olsen, Joy E.; FitzGerald, Tara L.; Cameron, Kate L.; Albesher, Reem A.; Mentiplay, Benjamin F.; Treyvaud, Karli; Burnett, Alice; Lee, Katherine J.; Pascoe, Leona; Roberts, Gehan; Doyle, Lex W.; et al.
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: The objective of this study was to determine whether school readiness differs between children born <30 weeks' gestation who are classified as at risk for developmental coordination disorder (DCD) and those who are not. Methods: This study was a prospective cohort study of children born <30 weeks' gestation. Children were classified as at risk for DCD at a corrected age of 4 to 5 years if they scored < 16th centile on the Movement Assessment Battery for Children–Second Edition (MABC-2), had a full scale IQ score of ≥80 on the Wechsler Preschool and Primary Scale of Intelligence–Fourth Edition (WPPSI-IV), and had no cerebral palsy. Children were assessed on 4 school readiness domains: (1) health/physical development [Physical Health domain of Pediatric Quality of Life Inventory (PedsQL), Pediatric Evaluation of Disability Inventory Computer Adaptive Test, and Little Developmental Coordination Disorder Questionnaire], (2) social-emotional development (Strengths and Difficulties Questionnaire and PedsQL psychosocial domains), (3) cognitive skills/general knowledge (WPPSI-IV), and (4) language skills (WPPSI-IV). Results: Of 123 children assessed, 16 were ineligible (IQ < 80 or cerebral palsy: n = 15; incomplete MABC-2: n = 1); 28 of 107 (26%) eligible children were at risk for DCD. Children at risk for DCD had poorer performance on all school readiness domains, with group differences of more than 0.4 SD in health/physical development, social-emotional development, and language skills and up to 0.8 SD for cognitive skills/general knowledge compared with those not at risk of DCD. Conclusion: Being at risk for DCD in children born <30 weeks' gestation is associated with challenges in multiple school readiness domains, not only the health/physical domain.